1995
DOI: 10.1159/000246590
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Angiocentric T-Cell Lymphoma Presenting as Lethal Midline Granuloma

Abstract: A case of angiocentric T-cell lymphoma with glabellar skin being the only affected site was reported. A 43-year-old woman had a several months’ history of glabellar swelling followed by progressive and destructive ulceration of the region. Histopathology of the biopsied specimen showed panniculitis with atypical lymphocytes and degenerative vessels filled with atypical cells. Most of the infiltrated lymphocytes were positive for CD2, CD3, CD4 and CD5. Antibodies to Epstein-Barr virus were detected in the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Interestingly, Jaffe et al 17 described rare cases that may present in the skin or soft tissue and relapse in the nose. In our review of the literature between 1983 and 1996, we found only 17 clear cases, 3,7,8,11,18,[21][22][23][24][25][26][27][28] of peripheral T-cell lymphoma with skin as well as nose metastasis. In six cases, 7,18,23,27,28 the lymphoma clearly proceeded from the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Jaffe et al 17 described rare cases that may present in the skin or soft tissue and relapse in the nose. In our review of the literature between 1983 and 1996, we found only 17 clear cases, 3,7,8,11,18,[21][22][23][24][25][26][27][28] of peripheral T-cell lymphoma with skin as well as nose metastasis. In six cases, 7,18,23,27,28 the lymphoma clearly proceeded from the skin.…”
Section: Discussionmentioning
confidence: 99%